Penerapan Pendekatan Contextual Teaching and Learning (CTL) dalam Pembelajaran Pendidikan Agama Islam dan Implikasinya terhadap Pengembangan Kemampuan Berpikir Kritis Siswa di SMAN 1 Sindangbarang - Nugraha, Mulyawan Safwandy; Dedih, Ujang; Mu’min, Wandi Syahrul (ALSYS, 2024)
Learning is actually a process of developing knowledge that students have to be prepared for life. Students are required to think critically and apply knowledge from the classroom to real life. Through the CTL approach, students are required to think critically in solving problems. In PAI subjects, students are always faced with things related to Allah SWT, fellow humans, and the environment. Therefore, the researcher took the initiative to apply the CTL approach to PAI subjects to develop students' critical thinking skills. This study uses a qualitative method with a qualitative descriptive approach. The subjects of the study are the Principal, PAI teachers, and students. The results of the study show that in the application of CTL to PAI learning at SMAN 1 Sindangbarang, PAI teachers have implemented learning innovations according to CTL demands by involving students in activities to relate the material to real situations. However, the implementation of the CTL approach still faces several obstacles, both from teachers, students, the environment, and institutions or the government. To overcome these obstacles, the school is working on MGMP, training, and other professional development. In order for the implementation of the PAI learning approach at SMAN 1 Sindangbarang to be carried out effectively, PAI teachers are required to have high professionalism. The implications for the development of students' critical thinking skills show that PAI learning at SMA N 1 Sindangbarang using the CTL method makes teaching and learning activities more effective. The concept of CTL directs students' reasoning to express opinions and arouse their independence and confidence.